Uji Aktivitas Antioksidan Ekstrak dan Fraksi Daun Rambutan (Nephelium lappaceum L.) dengan Metode FRAP (Ferric Reducing Antioxidant Power) serta Penetapan Flavonoid Total - Pratiwi, Dian; Tatiana Siska Wardani; Bagas Ardiantoro (Pusat Riset dan Inovasi Nasional, 2025)
Free radicals are unstable and highly reactive molecules that can cause oxidative stress, leading to cell damage and the development of degenerative diseases such as cancer, cardiovascular disorders, diabetes, and premature aging. To counteract these harmful effects, antioxidant compounds are required to inhibit oxidative reactions and protect cellular structures. Rambutan leaves (Nephelium lappaceum L.) are rich in bioactive compounds, including flavonoids, tannins, and saponins, which are reported to have strong antioxidant potential. The objective of this study was to evaluate the antioxidant activity of rambutan leaf extracts and their fractions, as well as to determine the IC₅₀ value using the Ferric Reducing Antioxidant Power (FRAP) method. Fractionation was performed using solvents of varying polarity, namely n-hexane, ethyl acetate, and water, to obtain different active fractions. Antioxidant activity was measured based on the ability of extracts and fractions to reduce Fe³⁺ ions to Fe²⁺ at a wavelength of 595 nm. The findings revealed that rambutan leaf extract exhibited very strong antioxidant activity, indicated by an IC₅₀ value of 20.65 ppm. Moreover, the activity increased proportionally with concentration, confirming a significant positive linear correlation. These results suggest that rambutan leaves are a promising natural source of antioxidants with potential applications in the development of pharmaceutical products, functional foods, and nutraceuticals aimed at preventing oxidative stress-related diseases.